2020
DOI: 10.1021/acs.oprd.0c00089
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Process for Preparing the Difluoromethylating Reagent [(DMPU)2Zn(CF2H)2] and Improved Synthesis of the ICHF2 Precursor

Abstract: Complex [(DMPU) 2 Zn(CF 2 H) 2 ] 1 is a crystalline organometallic reagent with utility in various catalytic difluoromethylation reactions under mild conditions. Unfortunately, this reagent is not commercially available and the procedure for the preparation of this air-and moisture-sensitive zinc complex has only been reported on a small scale. Herein, we report the development of a continuous process for the preparation of reagent 1 on >100 g scale by using a continuous stirred-tank reactor. The key to succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…We reason that the transmetallation of aCu I catalyst 1 with az inc-difluoromethyl reagent, (DMPU) 2 Zn-(CF 2 H) 2 2,i.e., Vicic-Mikami reagent, [21b,d] could form aC u I -CF 2 Hspecies 3.Notably,ahectogram synthesis of 2 has been recently reported by Pfizer. [24] Our previous work has suggested that Cu I -CF 2 Hs pecies 3 was as trong reductant (cal'd E red = À1.2 Vvs. SCE).…”
Section: Resultsmentioning
confidence: 97%
“…We reason that the transmetallation of aCu I catalyst 1 with az inc-difluoromethyl reagent, (DMPU) 2 Zn-(CF 2 H) 2 2,i.e., Vicic-Mikami reagent, [21b,d] could form aC u I -CF 2 Hspecies 3.Notably,ahectogram synthesis of 2 has been recently reported by Pfizer. [24] Our previous work has suggested that Cu I -CF 2 Hs pecies 3 was as trong reductant (cal'd E red = À1.2 Vvs. SCE).…”
Section: Resultsmentioning
confidence: 97%
“…We reason that the transmetallation of a Cu I catalyst 1 with a zinc‐difluoromethyl reagent, (DMPU) 2 Zn(CF 2 H) 2 2 , i.e., Vicic‐Mikami reagent, [21b, d] could form a Cu I ‐CF 2 H species 3 . Notably, a hectogram synthesis of 2 has been recently reported by Pfizer [24] . Our previous work has suggested that Cu I ‐CF 2 H species 3 was a strong reductant (cal′d E red =−1.2 V vs. SCE) [25] .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, Pfizer recently developed a scalable synthesis of [(DMPU) 2 Zn(CF 2 H) 2 ] (Scheme 67). 210 One of the key challenges to overcome was the high price of the starting material (CF 2 HI). To combat this problem, the synthesis of CF 2 HI from BrF 2 CCO 2 H was optimised.…”
Section: Industrial State Of Playmentioning
confidence: 99%